Pembuatan Animate 3D AM Band (Animation Band) - Assidiqi, Irvan Maulana; Fris Okta Falma (CV.ITTC INDONESIA, 2025)
This study aims to design and produce a 3D animation titled AM BAND as an educational medium based on interactive multimedia. AM BAND is a virtual band that performs the song “Animasi UNP” with digitally animated characters synchronized to the music. The production process includes stages of modeling, rigging, animating, texturing, lighting, rendering, and editing, utilizing Blender and Mixamo. The development method employed is the linear (Waterfall) model, supported by SWOT analysis techniques. The final result demonstrates strengths in visual and educational aspects, although certain technical challenges remain. This product is expected to serve as a creative and inspirational reference for digital animation learning within academic settings.